(untitled) (Anclajes, 2021)
The articles included in this dossier propose an analysis of transatlantic relations between Latin America, Italy and Spain, specifically in the 20th and 21st centuries. From a transdisciplinary approach, they examine both intertextual and personal links and, therefore, also analyze specific figures, institutions, and cultural mediation groups.